Have Standard VARs Remained Stable Since the Crisis? - Knut Are Aastveit; Andrea Carriero; Todd E. Clark; Massimiliano Marcellino (Norges Bank, 2014)
Small or medium-scale VARs are commonly used in applied macroeconomics for forecasting and evaluating the shock transmission mechanism. This requires the VAR parameters to be stable over the evaluation and forecast sample, or to explicitly consider parameter time variation. The earlier literature focused on whether there were sizable parameter changes in the early 1980s, in either the conditional mean or variance parameters, and in the subsequent period till the beginning of the new century. In this paper we conduct a similar analysis but focus on the effects of the recent crisis. Using a range of techniques, we provide substantial evidence against parameter stability. The evolution of the unemployment rate seems particularly different relative to its past behavior. We then discuss and evaluate alternative methods to handle parameter instability in a forecasting context. While none of the methods clearly emerges as best, some techniques turn out to be useful to improve the forecasting performance.
hdl:11250/2495970
Keywords: E17; C11; C33; C53; 330; Bayesian VAR; forecasting; time-varying parameters; stochastic volatility